2019
DOI: 10.1186/s12864-019-5558-8
|View full text |Cite
|
Sign up to set email alerts
|

Systems based analysis of human embryos and gene networks involved in cell lineage allocation

Abstract: Background Little is understood of the molecular mechanisms involved in the earliest cell fate decision in human development, leading to the establishment of the trophectoderm (TE) and inner cell mass (ICM) stem cell population. Notably, there is a lack of understanding of how transcriptional networks arise during reorganisation of the embryonic genome post-fertilisation. Results We identified a hierarchical structure of preimplantation gene network modules around the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Concern has been raised (Stirparo, et al, 2018) about the heterogeneity of tissue classification in the 373 single cell RNAseq data from Petropoulos et al (Petropoulos, et al, 2016). Our work broadly supports 374 these observations but also highlights that tissue classification can be made despite concerns in the 375 sample preparation (Stirparo, et al, 2018) or in inter individual differences (Smith, et al, 2019). This 376 observation would suggest that rigid definitions of tissue specific expression are not necessarily 377 helpful as we expand into single cell analysis.…”
Section: Similarities and Differences In Topology Between Human Embrysupporting
confidence: 56%
See 1 more Smart Citation
“…Concern has been raised (Stirparo, et al, 2018) about the heterogeneity of tissue classification in the 373 single cell RNAseq data from Petropoulos et al (Petropoulos, et al, 2016). Our work broadly supports 374 these observations but also highlights that tissue classification can be made despite concerns in the 375 sample preparation (Stirparo, et al, 2018) or in inter individual differences (Smith, et al, 2019). This 376 observation would suggest that rigid definitions of tissue specific expression are not necessarily 377 helpful as we expand into single cell analysis.…”
Section: Similarities and Differences In Topology Between Human Embrysupporting
confidence: 56%
“…Transcriptional analysis of isolated ICM and TE samples from individual human embryos has also been 36 performed, highlighting key metabolic and signalling pathways (Adjaye, et al, 2005). A recent study 37 of 1529 individual cells from 88 human preimplantation embryos defined a transcriptional atlas of this 38 stage of human development (Petropoulos, et al, 2016), however cell lineage allocation can be 39 problematic and inter-individual heterogeneity has been shown to have a major effect on gene 40 expression (Smith, et al, 2019;Stirparo, et al, 2018). Together these data show the relevance of 41 transcriptome based analysis and highlight the need for approaches that account for inter-individual 42…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling and analysis is emerging as a promising tool to improve the understanding and, thereby, assessment of what determines the quality of the embryo. Many researchers have attempted to characterize the expression profile of protein-coding genes at different stages of early embryogenesis [ 11 , 54 , 55 ]. SncRNAs are important regulators of their expression at the transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even with the same genetic background, with the use of multiple systems biologic approaches to compare developmental stages in the early human embryo with single-cell transcript data from blastomeres, it was shown that blastomeres considered to be totipotent were not transcriptionally equivalent [ 22 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%